Metro Manila Urban Transportation Strategy Planning Project, area traffic management improvements implementation report, vol. 2, part b1 implementation ;project prioritization, refinement and adoption (JPak-Poy & Kneebone Pty Ltd, 1986)
This volume contains Implementation Reports for area Traffic Management Improvements Projects developed as part as of the Metro Manila Urban Transportation Strategy Planning Project (MMUTSTRAP) Part B1 - Implementation Phase.